2016
DOI: 10.1016/j.juro.2015.12.089
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Abdominal Sacrocolpopexy: A Randomized, Controlled Trial

Abstract: Laparoscopic sacrocolpopexy provides outcomes as good as those of abdominal sacrocolpopexy for anatomical correction but not for anterior pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
75
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 22 publications
4
75
2
Order By: Relevance
“…Most previous studies have found that the laparoscopic and open approaches have similar anatomical outcomes but that the laparoscopic approach has the advantages of less blood loss and shorter hospital stay [1][2][3][4]. However, one recently published RCT found that the open approach has an anatomical advantage in the anterior compartment at 3 years [5]. The primary outcome in the present study was disease-specific quality of life measured using the Urinary Distress Inventory (UDI) at 12 months.…”
mentioning
confidence: 77%
“…Most previous studies have found that the laparoscopic and open approaches have similar anatomical outcomes but that the laparoscopic approach has the advantages of less blood loss and shorter hospital stay [1][2][3][4]. However, one recently published RCT found that the open approach has an anatomical advantage in the anterior compartment at 3 years [5]. The primary outcome in the present study was disease-specific quality of life measured using the Urinary Distress Inventory (UDI) at 12 months.…”
mentioning
confidence: 77%
“…Abdominal Sacral colpopexy (ASC) has a reputation for being the cornerstone in repairing the vault prolapse [7], furthermore, it has an important place in restoring the multicompartment pelvic organs herniation [7], and the recurrence protruded organs. The laparoscopic approach has highlighted the increasing benefit of this procedure by magnification and minimal invasion [7].…”
Section: Introductionmentioning
confidence: 99%
“…The laparoscopic approach has highlighted the increasing benefit of this procedure by magnification and minimal invasion [7]. Studies conducted to compare the laparotomic and the laparoscopic sacrocolpopexy(LSC) concluded that the surgery outcomes were similar with some limitation for both sides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations